The Usage and Attitude Towards Aspirating Dental Syringe, A Cross Sectional Study of Dental Practitioners in Khyber Pukhtunkhwa - Tajud Din, Soulat Jehan, Rida Ul Haya, Tariq Sardar, Muhammad Salman Khan, Ayesha Ilyas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of the study was to determine the usage and attitude toward aspirating dental syringes among dental practitioners in Khyber Pakhtunkhwa province of Pakistan. Study design: Descriptive, cross sectional Place and Duration: Rural Health Centre Koghuzi, February 2021 to May 2022. Methodology: A cross sectional conducted on dental practitioners in Khyber Pakhtunkhwa. A purpose developed, self-administered questionnaire was used to collect data. It included both open and close ended questions. SPSS version 23 was used and data were analyzed using Chi-square test. Results: 40.7% of respondents were qualified as specialist and the 59.3% were general practitioners. Only 31.6% of the dental practitioners have dedicated aspirating syringe available to them. Overall only 6.9% of the dental practitioners practice aspiration in all injection types. Most respondents agree that use of aspirating syringes contributes to safety of local anesthesia but only few think they had complication in their practice resulting from use of non-aspirating syringes. Most respondents think the might consider using aspirating syringes in the future. Conclusion: Despite the generally positive attitude towards aspirating syringes, few dental practitioners have dedicated aspirating syringe available to them and even few actually practice aspiration during local anesthesia. Keywords: Attitude, Local anesthesia, Aspiration, Aspirating dental syringes,